2012
DOI: 10.1021/jp3100377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on the Carbon Dioxide Absorption by 1-Alkyl-3-methylimidazolium Acetate Ionic Liquids

Abstract: The absorption of carbon dioxide by the pure ionic liquids 1-ethyl-3-methylimidazolium acetate ([C(1)C(2)Im][OAc]) and 1-butyl-3-methylimidazolium acetate ([C(1)C(4)Im][OAc]) was studied experimentally from 303 to 343 K. As expected, the mole fraction of absorbed carbon dioxide is high (0.16 at 303 K and 5.5 kPa and 0.19 at 303 and 9.6 KPa for [C(1)C(2)Im][OAc] and [C(1)C(4)Im][OAc], respectively), does not obey Henry's law, and is compatible with the chemisorption of the gas by the liquid. Evidence of a chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 27 publications
(59 reference statements)
8
106
2
1
Order By: Relevance
“…43 The authors concluded that "the overall tendency is that adding a certain amount of water into the pure ionic liquids will slightly decrease the absorption capacity of CO 2 , but the lower viscosity of the mixture is favourable as it can promote gas diffusion in the solvent and reduce operational constrains on the use of ionic liquids fluids". 62,64 Of the multitude of papers on carbon dioxide solubility in ionic liquids, those that mention water content, with very few exceptions, state that the ionic liquids must be as dry as possible. 62,64 Of the multitude of papers on carbon dioxide solubility in ionic liquids, those that mention water content, with very few exceptions, state that the ionic liquids must be as dry as possible.…”
Section: Anhydrous Carboxylate Ionic Liquidsmentioning
confidence: 99%
“…43 The authors concluded that "the overall tendency is that adding a certain amount of water into the pure ionic liquids will slightly decrease the absorption capacity of CO 2 , but the lower viscosity of the mixture is favourable as it can promote gas diffusion in the solvent and reduce operational constrains on the use of ionic liquids fluids". 62,64 Of the multitude of papers on carbon dioxide solubility in ionic liquids, those that mention water content, with very few exceptions, state that the ionic liquids must be as dry as possible. 62,64 Of the multitude of papers on carbon dioxide solubility in ionic liquids, those that mention water content, with very few exceptions, state that the ionic liquids must be as dry as possible.…”
Section: Anhydrous Carboxylate Ionic Liquidsmentioning
confidence: 99%
“…Indeed, a recent study that combined experimental data with a molecular simulation for the system [EMIM][OAc]/H 2 O indicated that the presence of water not only reduced the (physical) solubility of the gas as it competed for the same solvation sites of the IL but also rendered the chemical reaction between the gas and the IL less favorable. 34 Investigations with Raman analysis at several water contents, CO 2 pressures, and temperatures are currently underway to [TCM] ILs, the almost 4-fold increase of the CO 2 absorption capacity along with the 10-fold increase of the CO 2 absorption rate when mixed with water makes them very promising materials for CO 2 capture. For that reason they were thoroughly investigated as potential solvents in the laboratory-scale device involving a mass transfer column.…”
Section: Resultsmentioning
confidence: 99%
“…High pressure densities have been reported for [bmim][Ac] by Stevanovic et al 48 and Safarov et al 49 Supporting Information, Figure S12 shows the relative deviations of those data. From the figure, both deviations were larger than the uncertainties of this work.…”
Section: Figure 4 Shows Relative Deviations For [Bmim][tf 2 N] Atmentioning
confidence: 88%